(untitled) (Research, Society and Development, 2022)
The primary purpose of this study is to express how emotional intelligence has a relevant influence on achieving a successful career. This article aims to explore the impact that emotional intelligence can have on the professional life of individuals, analyzing the role of the emotional psychologist in this process. A bibliographic research was conducted based on books, with contributions from authors such as Goleman, Chiavenato and Campos, highlighting the importance of good management of emotional intelligence and its continuous evolution so that the individual can achieve success both in personal and professional life, which can be considered the apex of self-realization. As a result, it can be observed the extremely important role that the organizational psychologist plays in the evolution of the employee in his/her work environment and also his/her responsibility to guarantee the employee a better quality of life at work and the promotion of his/her mental health. It was also concluded that organizations have an essential role in the expansion of the emotional intelligence of their employees in the organizational environment since benefits will be attracted to the company itself.